Retrospective analysis of Plasmodium vivax genomes from a pre-elimination China inland population in the 2010s - Liu, Ying; Zhang, Tao; Chen, Shen-Bo; Cui, Yan-Bing; Wang, Shu-Qi; Zhang, Hong-Wei; Shen, Hai-Mo; Chen, Jun-Hu (Frontiers in Microbiology, 2023)
In malaria-free countries, imported cases are challenging because interconnections with neighbouring countries with higher transmission rates increase the risk of parasite re-introduction. Establishing a genetic database for rapidly identifying malaria importation or reintroduction is crucial in addressing these challenges. This study aimed to examine genomic epidemiology during the pre-elimination stage by retrospectively reporting whole-genome sequence variation of ten Plasmodium vivax isolates from inland China. The samples were collected during the last few inland outbreaks from 2011 to 2012 when China implemented a malaria control plan. China’s inland populations were highly structured compared to the surrounding area, with a single potential ancestor. Additionally, we identified genes under selection and evaluated the selection pressure on drug-resistance genes. In the inland population, positive selection was detected in some critical gene families, including sera, msp3, and vir. Meanwhile, we identified selection signatures in drug resistance, such as ugt, krs1, and crt, and noticed that the ratio of wild-type dhps to dhfr-ts increased after China banned sulfadoxine-pyrimethamine (SP) for decades. In short, our data provides an opportunity to investigate the molecular epidemiology of pre-elimination inland malaria populations, which exhibited lower selection pressure on invasion and immune evasion genes than neighbouring areas, but increased drug resistance in low transmission settings. Such findings could provide a genetic basis for future population studies, assessing changes in other pre-elimination countries.